ChemInform Abstract: Two New Four‐Connected Zeolite‐Like Magnesium Aluminophosphates with Intersecting 8‐Ring Channels. Issue 11 (March 2015) - Wang, Y. Y.; Mu, Y.; Sun, Y. J.; Li, J. Y.
Abstract Two new Mg‐containing aluminophosphates, (H2pip) [Mg2Al6(PO4)8 (H2O)4] (pip: piperazine) are hydrothermally obtained from gels of overall molar compositions of 1.0Al2O3:0.67MgO:2.91P2O5 :1.7pip:224H2O (I) or 1.0Al2O3:0.67MgO:2.62P2O5 :2.63pip:224H2O (II) differing slightly in the H3PO4 and piperazine amounts (autoclave, 180 °C, 3 d).